Politics and feminism: An introduction - Arneil, Barbara (Blackwell, 1999)
This book addresses the question of gender and feminism in western political theory and practise. It provides students with both the theoretical and historical underpinnings of women's exclusion from politics, and the feminist response to this exclusion.
Keywords: amériques; approches et analyses; cours; discipline; discriminations; europe; fem1000; histoire et politique; inégalités; occident; premier cycle; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; théories féministes; théories politiques

L’économie politique du sexe : transactions sur les femmes et systèmes de sexe/genre - Rubin, Gayle (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 1998)
La littérature sur les femmes — tant féministe qu’antiféministe — est une longue rumination quant à la nature et à la genèse de leur oppression et de leur subordination sociale. La question n’est pas sans importance, car les réponses qui lui sont données déterminent la manière dont nous envisageons l’avenir et si nous jugeons réaliste ou non d’espérer une société égalitaire entre les sexes. Plus important, l’analyse des causes de l’oppression des femmes fonde toute estimation de ce qu’il faudrait exactement changer pour réaliser une société sans hiérarchie de genre
Première publication: 1975 http://journals.openedition.org/cedref/171
Keywords: 1900-1999; 1960-1969; 1970-1979; anthropologie; approches et analyses; capitalisme; classe ouvrière; cours; discipline; europe; famille; fem1000; france; féminisme matérialiste; histoire et politique; inégalités; marxisme; patriarcat; premier cycle; psychanalyse; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences; sciences humaines; soc1016; soc2014; sociologie; systèmes d'oppressions; thématiques; théories féministes

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Minnesota University Press, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Contenu: Introduction / Aamir Mufti and Ella Shohat – pt. I. Contesting Nations. 1. Zionism from the Standpoint of Its Victims / Edward W. Said. 2. Sephardim in Israel: Zionism from the Standpoint of Its Jewish Victims / Ella Shohat. 3. Of Balkans and Bantustans: Ethnic Cleansing and the Crisis in National Legitimation / Rob Nixon. 4. "No Longer in a Future Heaven": Gender, Race, and Nationalism / Anne McClintock. 5. Currying Favor: The Politics of British Educational and Cultural Policy in India, 1813-54 / Gauri Viswanathan. 6. The Nation as Imagined Community / Jean Franco – pt. II. Multiculturalism and Diasporic Identities. 7. On the Question of a Theory of (Third) World Literature / Madhava Prasad. 8. Caliban Speaks Five Hundred Years Later / Roberto Fernandez Retamar. 9. The Local and the Global: Globalization and Ethnicity / Stuart Hall. 10. Multiculturalism and the Neoconservatives / Robert Stam. 11. Shuckin' Off the African-American Native Other: What's "Po-Mo" Got to Do with It? / Wahneema Lubiano. 12. Identity, Meaning, and the African-American / Michael Hanchard. 13. Just Looking for Trouble: Robert Mapplethorpe and Fantasies of Race / Kobena Mercer – pt. III. Gender and the Politics of Race. 14. Under Western Eyes: Feminist Scholarship and Colonial Discourses / Chandra Talpade Mohanty. 15. Traddutora, Traditora: A Paradigmatic Figure of Chicana Feminism / Norma Alarcon. 16. American Indian Women: At the Center of Indigenous Resistance in Contemporary North America / M. Annette Jaimes and Theresa Halsey. 17. "On the Threshold of Woman's Era": Lynching, Empire, and Sexuality in Black Feminist Theory / Hazel V. Carby. 18. Making Empire Respectable: The Politics of Race and Sexual Morality in Twentieth-Century Colonial Cultures / Ann Laura Stoler. 19. Age, Race, Class, and Sex: Women Redefining Difference / Audre Lorde. 20. Gender Is Burning: Questions of Appropriation and Subversion / Judith Butler. 21. Sisterhood: Political Solidarity between Women / Bell Hooks – pt. IV. Postcolonial Theory. 22. Not You/Like You: Postcolonial Women and the Interlocking Questions of Identity and Difference / Trinh T. Minh-ha. 23. Is the "Post-" in "Postcolonial" the "Post-" in "Postmodern"? / Kwame Anthony Appiah. 24. The World and the Home / Homi K. Bhabha. 25. Reading Africa through Foucault: V.Y. Mudimbe's Reaffirmation of the Subject / Manthia Diawara. 26. Teaching for the Times / Gayatri Chakravorty Spivak. 27. Postcolonial Criticism and Indian Historiography / Gyan Prakash. 28. The Postcolonial Aura: Third World Criticism in the Age of Global Capitalism / Arif Dirlik. Le texte "Age, Race, Class, and Sex : Women Redefining Difference" de Audre Lorde a été donné en lecture au cours LIT4700.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Killing the Black Body: race, reproduction, and the meaning of liberty - Roberts, D. (Pantheon, 1997)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; histoire et politique; inégalités; justice reproductive; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

La Voz de la mujer: periódico comunista-anárquico, 1896-1897 - Universidad Nacional de Quilmes (Universidad Nacional de Quilmes, 1997)
La Voz de la Mujer, La Voix de la femme en français, est le premier journal anarcha-féministe au monde. Publié en Argentine par un collectif de femmes dont la communiste libertaire Virginia Bolten, il compte neuf numéros, parus du 8 janvier 1896 au 10 mars 1897. (Wikipedia)
Disponible gratuitement en ligne https://www.marxists.org/espanol/tematica/kiosko/argentina/voz-de-la-mujer/index.htm
Keywords: 1800-1899; 1890-1899; amérique latine; amériques; approches et analyses; argentine; cours; droits des femmes*; histoire et politique; inégalités; justice sociale; lit3220; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

A diplomacy of the oppressed: New directions in international feminism - Ashworth, Georgina (Zed Books, 1995)
Les contributrices abordent les problèmes du mouvement international des femmes, tels que la résolution des conflits; la violence; zones de libre-échange ; l'environnement; culture et identité nationale; santé; les média; droits humains; et l'emploi, en mettant l'accent sur la situation des femmes dans toutes les régions du monde. Destiné aux étudiants en études féministes, en sciences politiques et en études du développement
Keywords: 1900-1999; anthologie; approches et analyses; conflit; coopérative internationale; cours; discipline; fem1000; genre; histoire; histoire et politique; identités LGBTQIA2+; inégalités; militance; mouvements des femmes*; mouvements féministes; premier cycle; périodes historiques; science politique; science politique et droit; sciences humaines; systèmes d'oppressions; thématiques

America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Un sujet inclassable? approches sociologiques, littéraires et juridiques des homosexualités - Mendès-Leite, Rommel ("Cahiers Gai-Kitsch-Camp, 1995)
Section: 211 pages : illustrations, couv. illustrations en couleur ; 21 cm
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droits; europe; france; histoire et politique; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; shm4000; systèmes d'oppressions; thématiques

Thunder in my soul: a Mohawk woman speaks - Monture-Angus, Patricia (Fernwood Publishing, 1995)
"This book contains the reflections of one Mohawk woman and her struggles to find a good place to be in Canadian society. The essays, written in enjoyable and accessible language, document the struggles against oppression that Aboriginal people face, as well as the success and change that have come to Aboriginal communities. It speaks to both the mind and the heart."–Résumé de l'éditeur.
Section: x, 273 pages ; 23 cm
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; mohawk; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques

Femmes : moitié de la terre, moitié du pouvoir - Halimi, Gisèle; femmes (Association), Choisir–la cause des (Gallimard, 1994)
Les 3 et 4 juin 1993, le mouvement Choisir-La cause des femmes, que préside Gisèle Halimi, a organisé au palais de l'Unesco, à Paris, un colloque international pour la parité femmes-hommes dans toutes les instances politiques de notre pays. Ce colloque a rassemblé une soixantaine de personnalités de vingt-deux pays (dont la Chine) parmi lesquelles plus de quarante femmes ministres, anciennes ministres, députées, anciennes députées, ambassadrices, présidentes de Parlements, ainsi que des historiennes, écrivaines, sociologues, politologues, juristes, etc. Ce sont les minutes de ce colloque qui sont ici publiées. La diversité des intervenantes - de Simone Veil à la secrétaire d'État américaine Hazel O'Leary, de la ministre israélienne Shulamith Aloni à la diplomate palestinienne Hanan Ashraoui - réunies pour promouvoir une «autre démocratie» donne à ce livre un caractère exceptionnel qui fera date et marque une nouvelle étape dans le combat des femmes pour la parité qui est aujourd'hui «l'idée neuve en Europe».
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; fem1000; femmes* politiques; histoire et politique; interdisciplinarité; international; inégalités; premier cycle; périodes historiques; systèmes d'oppressions; thématiques; égalité femme*-homme

«Débat». Femmes et histoire : Colloque, La Sorbonne, 13-14 novembre 1992 - Farge, Arlette; Perrot, Michelle (Femmes et histoire : Colloque, La Sorbonne, 13-14 novembre 1992, 1993)
Commencée fin 1987, « L’histoire des femmes en Occident » vient de s’achever. Ce travail collectif international d’une grande ampleur - 5 volumes, 3 000 pages écrites par 72 auteurs - constitue à ce jour l’effort le plus achevé pour affirmer la légitimité d’un champ de recherche : l’approche sexuée de l’histoire de nos sociétés. Publiée en 9 langues, cette entreprise a suscité aussitôt un immense intérêt, signe incontestable d’une demande sociale forte. Mais cette approche historique pose beaucoup de questions : sur la pertinence de la chronologie classique, sur la notion d’Occident et son étroitesse, sur la validité des sources, sur la fonction des images, sur la difficulté à saisir autre chose qu’une représentation construite majoritairement par les hommes, sur le consentement des femmes à leur rôle, sur la notion de pouvoirs, sur celle de progrès... Prolongement critique de « L’histoire des femmes en Occident », le colloque « Femmes et Histoire » est la manifestation d’une réflexion ouverte et actuelle qui ne demande qu’à se poursuivre.
Keywords: approches et analyses; cours; discipline; fem1000; histoire; histoire des femmes*; histoire et politique; inégalités; occident; premier cycle; rapports sociaux de sexe; sciences humaines; sexisme; systèmes d'oppressions; thématiques

Pourquoi n'y-a-t-il pas eu de grands artistes femmes? - Nochlin, Linda (Femmes, art et pouvoir., 1993)
Première publication : 1991
Keywords: approches et analyses; arts; cours; discipline; domination masculine; fem1000; histoire de l'art; histoire et politique; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; théories féministes

Mais qu’est-ce qu’elles disent ? - Picq, Françoise (Libération des femmes: les années-mouvement, 1993)
Le 26 août 1970 à l'Arc de Triomphe, neuf femmes donnaient par une action symbolique le coup d'envoi d'un mouvement qui allait en une quinzaine d'années bouleverser profondément la société française.A partir de son expérience personnelle, de l'étude des écrits et des archives du Mouvement de libération des femmes, d'une enquête auprès des féministes de la première heure, Françoise Picq présente ici une histoire en trois temps : celui de la découverte, celui des contradictions, puis le temps de la réflexion et du bilan avec les années quatre-vingt.
Section: 380 pages ; 22 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire et politique; inégalités; militance; mouvements de femmes*; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques

Nothing mat(t)ers: A feminist critique of postmodernism - Brodribb, Somer (J. Lorimer, 1992)
Nothing Mat(t)ers est une critique féministe des théories de Foucault, Derrida et Lacan, entre autres. Somer Brodribb analyse les textes et les arguments que le poststructuralisme a désignés comme centraux, exposant ainsi la misogynie en leur cœur. Brodribb fournit une histoire des définitions du structuralisme, du poststructuralisme, de la déconstruction et du postmodernisme
Keywords: approches et analyses; cours; discours dominant; fem1000; genre; histoire et politique; identités LGBTQIA2+; inégalités; patriarcat; postmodernisme; premier cycle; ressource en ligne; systèmes d'oppressions; thématiques

In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty–and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Papers of the "Forth Hill Conference on Southern Culture", held at Clemson Univ. (1989). Textes de Fort Hill Conference on Southern Culture, tenue à Clemson University au printemps de 1989.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)